2013
DOI: 10.1152/ajpcell.00305.2012
|View full text |Cite
|
Sign up to set email alerts
|

Elevated SOCS3 and altered IL-6 signaling is associated with age-related human muscle stem cell dysfunction

Abstract: McKay BR, Ogborn DI, Baker JM, Toth KG, Tarnopolsky MA, Parise G. Elevated SOCS3 and altered IL-6 signaling is associated with age-related human muscle stem cell dysfunction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
76
2

Year Published

2014
2014
2016
2016

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 72 publications
(82 citation statements)
references
References 64 publications
3
76
2
Order By: Relevance
“…Subject characteristics have been published previously for the groups used in the present study (21). There were no differences in lean body mass with age (20,21).…”
Section: Resultsmentioning
confidence: 74%
See 2 more Smart Citations
“…Subject characteristics have been published previously for the groups used in the present study (21). There were no differences in lean body mass with age (20,21).…”
Section: Resultsmentioning
confidence: 74%
“…Eighteen community-dwelling, untrained younger (Y; n ϭ 9, 21 Ϯ 3 yr) and older (O; n ϭ 9, 70 Ϯ 4 yr) men were recruited to complete a single RE bout, as described previously (20,21). Participants underwent a routine screening before the study and were required to complete a health questionnaire and not to have been involved in a lower-body RE program for at least 6 mo before the study.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, It has been shown previously that IL-6 is a pivotal regulatory factor for muscle stem cell proliferation in both young men and animals (Toth et al, 2011) but it is important to highlight that the appearance of elevated IL-6 was transient following muscle damage (Toth et al, 2011). Meanwhile in healthy elderly, IL-6 has been shown to be chronically elevated (Alvarez-Rodriguez et al, 2012), which in turn may impair the normal IL-6 response and the sensitivity of the stem cells to this cytokine (McKay et al, 2013). Different reports have shown that chronic systemic elevation of IL-6 leads to muscle atrophy in aging and disease states (Baltgalvis et al, 2008).…”
Section: Chronic Inflammationmentioning
confidence: 99%
“…Importantly, muscle function or quality appears to be reduced in aged muscle, displaying a decrease in power and maximum force production even when corrected to cross-sectional area (Brooks and Faulkner 1988 ). Although it is unclear at present whether there is an age-related reduction in the satellite cell pool size, it is clear that aging is accompanied by an impairment in the response of satellite cells to myotrauma in humans (Dreyer et al 2006 ;McKay et al 2013 ;McKay et al 2012 ) and animals . Satellite cells have been implicated as a signifi cant factor contributing to the inability of the muscle to repair/ remodel.…”
Section: Muscle Stem Cells and Agingmentioning
confidence: 99%